DESIGN AND DEVELOPMENT OF MOBILE CHARGING SYSTEM USING THERMOELECTRICITY - Almawgani, A. H. M.; Hindi, A. T.; Irfan, Muhammed; Alghamidi, Hisham; Rahman, Saifur (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Energy sources differ throughout the world-, as do the costs of acquiring those sources. Electric energy has become an important element in our daily lives, especially for those devices that cannot be eliminated due to necessity. The usage of mobile phones has become an important element of our lives and their battery consumption is increasing due to the installation of a variety of Android applications. Electricity is required to charge the battery of the mobile phone; however, and at times, while travelling in a remote area there might not be access to electricity. Thus, the mobile would not be able to recharged. This paper presents the idea to design a mobile charging system using thermoelectricity. The thermal energy from the human body has been utilized to generate the electric power needed for the mobile charging process. To do this, a Peltier circuit device is connected to the human body. The difference in temperature between the human body and the atmosphere generates the voltage at the output of the Peltier circuit. The output from the Peltier circuit is then given to the boost converter and amplified to generate 5 volts which in turn are used to charge the mobile.